Types of Yes – No Questions Found in the Movie 500 Days of Summer - Dita Rusanti, Apri (Humanis; Vol 22 No 4 (2018), 2018)
Abstract The paper entitled “Types of Yes-No Question Found in  the movie “500 Days of Summer” focuses on types of the English interrogative sentences especially yes-no question form s and their functions used in the movie 500 Days of Summer in 2009. The data were analyzed qualitatively in accordance with some relative theories. The theories used for this study are the theories of English yes-no questions taken from “Comprehensive Grammar of the English Language” by Quirk (1985) and “A Practical English Grammar” by Thomson A.J and A.V Martinet  (1986). Then the data were presented descriptively by explaning the process and the result of discussion.Based on the findings there are five forms of English yes-no question s found in the data belonging to the Major classes of questions. Those English yes-no question s found in the data were possitive yes-no question s , negative yes-no question s , declarative questions, tag questions, yes-no questions with modal auxiliaries. The data were analyzed and some functions of the interrogative sentence were found : (a) Asking for request;(b) Confirmation; (c) Offering; (d) Asking for information; (f) Asking for permission .Mostly yes-no question s found in the data are asking for information and confirmation. However, suggestion and greeting do not exist in the data.